Decomposition characteristics of methane hydrate in porous media under continuous and intermittent microwave heating. (15th January 2023) - Zhu, Yue; Li, Xuhui; Zhao, Chuang; Zhang, Jing; Bondarenko, Volodymyr; Dreus, Andrii; Liang, Jinqiang; Li, Xiaoyang; Zhu, Jinlong; Wang, Pengfei; Li, Shengli; Liu, Baochang
Highlights: Factors affecting methane hydrate decomposition under microwave heating are studied. Hydrate decomposition time decreased with increase in microwave power. Heating cycle invovled 5 min of microwave stimulation and 1 min of no stimulation. This intermittent microwave heating improved the efficiency ratio by 59.32%. Abstract: Microwave stimulation is a new method for natural gas hydrate exploitation. In this study, methane hydrate was synthesized in quartz sand with a particle size of 106–150 μm, and the decomposition characteristics were investigated using continuous and intermittent microwave heating. During the initial stage of continuous microwave heating, methane hydrate decomposed immediately due to microwave stimulation. Subsequently, due to a decrease in microwave penetration depth, microwaves did not affect the areas further away from the microwave source and macroscopic heat transfer became the main heat source for hydrate decomposition. The microwave power used during the study ranged from 200 W to 500 W. The results indicated that hydrate decomposition time decreased as power increased, and the average gas production rate increased at the same time. However, the energy efficiency ratio did not vary with the microwave power. The maximum energy efficiency ratio was 1.320 at a microwave power of 400 W under continuous microwave heating. Compared with continuous microwave heating, intermittent microwave heating improved the efficiency ratio by 59.32 %, with a heating cycle involving microwave stimulation for 5 min (Microwave ON time) and no stimulation for 1 min (Microwave OFF period). As microwaves provide heat for hydrate decomposition, a high-speed gas production can be obtained. Heat reservoirs were utilized to maintain hydrate decomposition during the OFF period, which also resulted in energy saving. Although intermittent microwave heating reduced the average gas production rate slightly, it improved the energy efficiency significantly. Therefore, the number of heating cycles and microwave heating periods should be carefully considered to obtain high hydrate exploitation efficiency. Intermittent microwave heating is recommended for hydrate exploitation to improve extraction efficiency and save energy.